2019
DOI: 10.1038/s41559-019-0864-8
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and genome of a snailfish from the Mariana Trench provide insights into deep-sea adaptation

Abstract: It is largely unknown how living organisms—especially vertebrates—survive and thrive in the coldness, darkness and high pressures of the hadal zone. Here, we describe the unique morphology and genome of Pseudoliparis swirei—a recently described snailfish species living below a depth of 6,000 m in the Mariana Trench. Unlike closely related shallow sea species, P. swirei has transparent, unpigmented skin and scales, thin and incompletely ossified bones, an inflated stomach and a non-closed skull. Phylogenetic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
143
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 117 publications
(183 citation statements)
references
References 97 publications
2
143
1
Order By: Relevance
“…These genomes has fueled a number of studies on the phylogeny and evolution of fish (e.g., the African coelacanth genome and tetrapod evolution), evolutionary processes of specific fish subgroups (e.g., elephant shark genome illustrating the phylogenetic relationship of Chondrichthyes as a sister group to bony vertebrates) [1], genetic mechanisms of adaptation to different environments (e.g. the deep-sea Mariana Trench snailfish and cave-dwelling fish) [2], and specific biological processes (for example, the tonguefish Cynoglossus semilaevis genome for understanding ZW sex chromosome evolution) [3]. Nevertheless, the current fish genome sequencing results are only a drop in the ocean, and numerous critical research questions remain to be resolved.…”
Section: Background Fish Genomes Sequenced To Datementioning
confidence: 99%
“…These genomes has fueled a number of studies on the phylogeny and evolution of fish (e.g., the African coelacanth genome and tetrapod evolution), evolutionary processes of specific fish subgroups (e.g., elephant shark genome illustrating the phylogenetic relationship of Chondrichthyes as a sister group to bony vertebrates) [1], genetic mechanisms of adaptation to different environments (e.g. the deep-sea Mariana Trench snailfish and cave-dwelling fish) [2], and specific biological processes (for example, the tonguefish Cynoglossus semilaevis genome for understanding ZW sex chromosome evolution) [3]. Nevertheless, the current fish genome sequencing results are only a drop in the ocean, and numerous critical research questions remain to be resolved.…”
Section: Background Fish Genomes Sequenced To Datementioning
confidence: 99%
“…A previous study showed that the osmolyte trimethylamine N-oxide (TMAO) helped snailfish stabilize proteins against pressure (Yancey et al, 2014). With the interpretation of the hadal snailfish genome, the mechanism underlying the adaptation of hadal snailfish to pressure has been understood from a new perspective (Wang et al, 2019). However, with regard to the characteristics of the hadal environment, in addition to pressure, nutrient acquisition, micronutrient biosynthesis and immune protection are also critical for organismal survival due to the low nutrient levels under normal conditions and the high abundance of unknown viruses and other potentially harmful microorganisms in the surrounding water compared to the surface (Hara et al, 1996;Yoshida et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Conditions on the deep-sea floor are poorly known but generally are considered too harsh for the survival of most organisms, e.g., high hydrostatic pressure, darkness, hypoxia, low temperature, and limited food availability [1][2][3][4][5]. However, a macrofauna consisting of a growing range of newly discovered animals adapted to deep-sea habitats has been reported, including crustaceans [6][7][8], polychaetes [9,10], fishes [11,12], and mollusks [13,14]. Various mechanisms have adapted them for survival in deep-sea environments: e.g., squat lobsters and mussels have developed chemoautotrophic systems of symbiotic bacteria for inhabiting hydrothermal vents and cold seeps in the seafloor [15][16][17]; and snailfish have evolved special morphological and physiological characters to survive and thrive in the hadal zone [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, a macrofauna consisting of a growing range of newly discovered animals adapted to deep-sea habitats has been reported, including crustaceans [6][7][8], polychaetes [9,10], fishes [11,12], and mollusks [13,14]. Various mechanisms have adapted them for survival in deep-sea environments: e.g., squat lobsters and mussels have developed chemoautotrophic systems of symbiotic bacteria for inhabiting hydrothermal vents and cold seeps in the seafloor [15][16][17]; and snailfish have evolved special morphological and physiological characters to survive and thrive in the hadal zone [12]. Studies aimed at understanding survival strategies and adaptive evolution of organisms living in deep seas have also employed genomic or transcriptomic sequencing.…”
Section: Introductionmentioning
confidence: 99%